2014
DOI: 10.1155/2014/145289
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Spindle Assembly Checkpoint Status in Oral Cancer

Abstract: Abnormal chromosome number, or aneuploidy, is a common feature of human solid tumors, including oral cancer. Deregulated spindle assembly checkpoint (SAC) is thought as one of the mechanisms that drive aneuploidy. In normal cells, SAC prevents anaphase onset until all chromosomes are correctly aligned at the metaphase plate thereby ensuring genomic stability. Significantly, the activity of this checkpoint is compromised in many cancers. While mutations are rather rare, many tumors show altered expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 76 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…The faithful segregation of genetic material into daughter cells during cell division is crucial for the production of healthy progeny (Jin et al, 2010;Whitfield et al, 2013;Teixeira et al, 2014). Chromosome segregation is regulated by several mechanisms, including cohesion degradation and SAC-dependent surveillance (Musacchio and Ciliberto, 2012).…”
Section: A Potential Role Of Cdc201 In Meiotic Chromosome Segregationmentioning
confidence: 99%
“…The faithful segregation of genetic material into daughter cells during cell division is crucial for the production of healthy progeny (Jin et al, 2010;Whitfield et al, 2013;Teixeira et al, 2014). Chromosome segregation is regulated by several mechanisms, including cohesion degradation and SAC-dependent surveillance (Musacchio and Ciliberto, 2012).…”
Section: A Potential Role Of Cdc201 In Meiotic Chromosome Segregationmentioning
confidence: 99%
“…Several studies reported that defects in SAC activity are linked to an increased rate of aneuploidization during tumorigenesis and that the expression levels of SAC proteins are altered in various human tumours and cell lines (Barbosa et al , ; Silva et al , ). However, our knowledge on SAC protein expression in oral cancer remains rather scarce (Teixeira et al , ). This study aimed at: (i) investigating the expression levels of BubR1 and Mad2 and its relationship to the competence of the SAC in OSCC cell lines; (ii) analysing the expression of BubR1 and Mad2 in OSCC tissue samples; and (iii) evaluating its clinicopathological significance.…”
Section: Introductionmentioning
confidence: 99%
“…A possible intrinsic repair mechanism cannot be discarded. Mitotic defects caused by environmental insults, such as viral infection, are monitored by the spindle assembly checkpoint, an evolutionarily conserved mechanism (Teixeira et al, 2014) that participates in a cascade of events that allows more time for cells to correct meiotic defects (Lawrence et al, 2015).…”
Section: Discussionmentioning
confidence: 99%